A novel approach to assess volumetric bone loss at immediate implant sites and comparison to linear measurements: A pilot study. (May 2022) - Chang, Chi-Ching; Kim, Sung K.; Lee, Chun-Teh
Highlights: CBCTs were largely utilized to evaluate alveolar bone dimensional alterations. Linear, instead of volumetric measurements were often used to demonstrate bone loss. Linear measurements may not fully represent real-life three-dimensional bone change. The center of the implant may not be the best location to make linear measurements. A novel workflow to render and analyze bone dimensional alteration was developed. Abstract: Objectives: Studies have evaluated changes in hard tissue following immediate implant placement (IIP) through cone beam computed tomography (CBCT) imaging. This study compared the 3D volumetric changes of the alveolar bone at immediate implant sites with 2D linear measurement outcomes by using a novel image analysis workflow. Methods: Preoperative and 6-month postoperative CBCT images of patients who underwent IIP and bone grafting in the maxillary esthetic area were acquired. Linear and volumetric measurements of buccal bone dimensions were taken using a specially designed workflow. The 2D and 3D measurements were compared, and their correlations were determined. Results: Images from 13 patients (13 implants) were analyzed. Linear measurements revealed that the general linear buccal bone loss was less than 1mm in all segments. The 3D volumetric bone reduction (reported as median [first quantile, third quantile]) in the vertical, cervical, middle, and apical segments was 14.27 [11.33, 30.66] mm 3 (51.30 [42.78, 66.91]%), 16.20 [10.35, 30.52] mm 3 (18.20 [9.88, 24.74]%), 17.48 [8.42, 21.17] mm 3 (24.05 [12.39, 28.22]%), and 6.87 [3.88, 9.45] mm 3 (11.34 [5.14, 22.54]%), respectively. Significant positive correlations between 2D and 3D measurements were consistently identified in the cervical and middle segments, but no significant correlation was noted in the vertical segment. Conclusions: The results revealed that linear measurements could not fully represent volumetric bone dimensional changes. Performing volumetric measurements and 3D rendering could be valuable in presenting the actual amount and topography of peri-implant bone remodeling. Clinical Significance: Linear measurements only partially represent the real-life event of 3D bone changes at immediate implant sites. Factors affecting hard tissue alterations following IIP should be reassessed using 3D volumetric measurement outcomes.